PENGARUH LIVE STREAMING ATTRIBUTES TERHADAP PERCEIVED JOY DAN BEHAVIORAL INTENTION PADA PENGGUNA LIVE STREAMING TIKTOK DI SURABAYA - Dharmayanti, Diah; Andrina, Anak Agung Ayu Puty (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Abstract: The purpose of this study is to examine and provide evidence of the influence of livestream attributes on perceived joy and behavioral intention among TikTok live stream users in Surabaya. This study employs the Structural Equation Modeling (SEM) technique based on Covariance-Based (CB) analysis to conduct path analysis using AMOS (Analysis of Moment Structure) software. The respondents in this study comprised 200 individuals who had used and made transactions through TikTok Shop live streaming, selected using a purposive sampling method. The research scope includes livestreaming attributes such as information task-fit, visual effect, and sociability as independent variables. The dependent variables are perceived joy and behavioral intention, while motivational mindset (promotion focus/prevention focus) serves as a moderating variable. The findings indicate that sociability is influenced by perceived joy; perceived joy significantly affects behavioral intention; and motivational mindset (promotion focus/prevention focus) moderates the relationship between perceived joy and behavioral intention. However, information task-fit and visual effect do not significantly influence perceived joy, and information task-fit and sociability do not significantly affect behavioral intention. Keywords: Live Streaming Attributes, Perceived Joy, Information Task-Fit, Visual Effect, Sociability, Behavioral Intention, Online Live Streaming Shopping